Comparison of Natural Dyes from Telang Flower Extracts (Clitoria ternatea L) as a Substitute for Methylen Blue in Diff Quik Painting - Elsa Nurita Azka; Andita Ayu Mandasari; Setyo Dwi Santoso (Universitas Muhammadiyah Sidoarjo, 2021)
Telang flower (Clitorea ternatea L) is a type of vine that grows wild in rice fields and has been widely used as food coloring. Telang flowers contain several active compounds, which is anthocyanin gives a blue color. This research was conducted with the aim of knowing the telang flower extract as a natural dye to substitute methylenen blue in diff quik painting. The analysis samples used were oral mucosal ephithelial cells which were taken by scraping the oral mucosa using cytobrush. Dried and mashed telang flower was then dissolved with distilled water (1:5) to make an extracts before the trial process of the samples. The results showed that the epithelial cells stained with methylene blue were better than telang flower extract. The immersion time of 15 minutes gave different colors to the cell nucleus and cytoplasm compared to 2 minutes and 5 minutes of immersion.